Executive functioning and daily living of individuals with chronic stroke: measurement and implications. Issue 2 (June 2018) - Lipskaya-Velikovsky, Lena; Zeilig, Gabi; Weingarden, Harold; Rozental-Iluz, Clara; Rand, Debbie
Abstract : Deficits in executive functioning (EF) are often still present at the chronic stage after stroke, which may negatively impact independent living. The objectives of this study were (a) to characterize the EF and independence in daily living of community-dwelling individuals with chronic stroke by using pen-and-paper and performance-based EF assessments, (b) to explore correlations between scores detected by different EF assessments and (c) to assess the correlations between EF and independence in basic activities of daily living (BADL) and instrumental activities of daily living (IADL). This cross-sectional study included 50 (30 men and 20 women) community-dwelling individuals [mean (SD) age 59.8 (9.3)] with chronic stroke. Participants were overall independent in basic activities of daily living, without significant cognitive impairment. Participants underwent EF assessment using two pen-and-paper tools: Trail Making Test, Zoo Map subtest from the Behavioral Assessment of Dysexecutive Syndrome and two performance-based tools; EF Route-Finding Task and bill-paying subtest from the Executive Functions Performance Test. BADL, IADL, depressive symptoms, gait speed and upper extremity motor impairment were also assessed. Participants demonstrated mild to moderate EF deficits with moderate significant correlations between the scores of various EF assessments. Participants varied in their independence in IADL, and EF was significantly correlated to independence in BADL and IADL (−0.31< r <0.48; −0.37< r <−0.42; P <0.05, respectively, depending on the assessment). EF deficits with varying severity are still present at the chronic stage after stroke among independent community-dwelling individuals. These findings can guide the choice of an appropriate assessment tool for the specific needs of individuals with chronic stroke.